Aedes aegypti and Aedes albopictus Ocurrences in Guatemala. (4th October 2017) - Lepe-Lopez, Manuel; Canet, Miriam; Davila, Marcela; Flores, Edson; Lopez, Yaimie; Davila, Amilcar; Escobar, Luis
Abstract: Background: Recent emergence of zika and chikungunya along with the continuous prevalence of dengue in Guatemala has become a threat to public health resulting in high morbidity and mortality. According to national epidemiologic vigilance reports, the prevalence for dengue, chikungunya, and zika are 53.42, 30.96, and 19.02 per 100, 000 habitants respectively. Despite cases of the diseases being reported countrywide, the regional occurrences of Aedes aegypti and Aedes albopictus are unknown, with some studies reporting the presence of the vectors in only four of 22 departments. Methods: National active larval entomologic surveillance information was obtained and the results where validated through Geographical Information Systems tools to generate a map of occurrences of either Aedes aegypti or Aedes albopictus . The information was compared with the reports of cases of the diseases associated with these vectors. Results: A albopictus (75 occurrences) and A aegypti (133 occurrences) were reported in 11 and 21 out of 22 departments, respectively. A second further directed active vigilance of stagnant water in cemeteries of the one department where the vectors were not found was done to corroborate their absence. This secondary vigilance showed the presence of Culex quinquefasciatus larvae. A aegypti was identified mostly in regions with low altitude and high temperature while A albopictus was most common in regions with high precipitation and high altitude. The departments with most occurrences are also the ones with highest case report prevalence. Conclusion: A possible correlation between number of vector occurrences per department and number of disease cases reported could exist; however, further studies taking into account population density and distribution, climatic change implications, and geographic characteristics are needed to establish such correlation. Furthermore, even though there is an apparent absence of the vectors in one department, there are still reports of the disease. These cases should be further analyzed to determine whether migration or clinical misdiagnosis is a possibility. These results highlight the importance of strict epidemiological vigilance of the vectors as a way to impact on the disease. Disclosures: All authors: No reported disclosures.